SEJARAH PERKEMBANGAN REGULASI PENYEMBELIHAN HALAL INDONESIA - Roselia F, Dyah Putri; Hafiz, Mulya (Institut Agama Islam Syubbanul Wathon Magelang, 2024)
Indonesia has a regulation of Halal Slaughter since 2014, the provisions applied must have standardization from various aspects, such as religious and modern aspects. Religion provides strict regulations regarding one slaughter incision, chanting the name of Allah and the animal is alive. Meanwhile, the slaughter industry has developed using the stunning process. Through a literature review by looking at the aspects that affect halala slaughter standards. Using descriptive analysis by looking at the provisions of existing regulations in Indonesia. The results of this study show that the historical regulation of slaughterhouses in Indonesia considers all aspects, namely religious and modern aspects. This regulation shows that regulations in Indonesia are more comprehensive in having halal slaughterhouses. This means that the development of slaughterhouse regulations since long ago reflects the government's commitment to religious rules.